Monumenta : Beelden en monumenten in de stad Antwerpen. - Cools, H.B.; Van Beneden, Ben; 1987/06/28 - 10/11, Middelheimmuseum Antwerpen (Antwerpen : Middelheimmuseum Antwerpen, 1987)
Beyaert, Henri ; Bierwerts, Willem ; Blomberg, Stig ; Bury, Pol ; Cantré, Jozef ; Charlier, Guillaume ; Courbier, J. ; Crick, Alfred ; De Braekeleer, Jacob ; Deckers, Edward ; De Cuyper, Jean-Baptiste ; De Cuyper, Leonard ; De Lalaing, Jacques ; de Leeuw, Bert ; Dries, Jan ; Ducaju, Jozef Jaak ; Dupon, Josué ; Dupuis, Louis ; Eickhoff, Gottfried ; Geefs, Jozef ; Geefs, Willem ; Goossens, Simon ; Grandmoulin, Léandre ; Hartung, Karl ; Herciger, Sam ; Ianchelevici, Idel ; Jespers, Oscar ; Joris, Frans ; Kreitz, Willy ; Lambau, Raoul ; Lambeaux, Jef ; Libonati, Francesco ; Lisberg, Hugo ; Marcks, Gerhard ; Martin, Raymond ; Mascherini, Marcello ; Meunier, Constantin ; Minne, George ; Palinck, Karel ; Pecher, Jules ; Peters, Jozef J. ; Poels, Albert ; Rubens, Pieter Paul ; Sauter, Rik ; Schott, Walter ; Smeesters, Diane ; Stojadinovic, Ratimir ; Van Averbeke, Emiel ; Heede, F. Van Den ; de Velde, Henry Van ; Van Esbroeck, Leopold ; Van Mechelen, Alexis ; Vereycken, Edouard ; Verlee, Luc ; Vindevogel, Georg ; Wallenberg, Axel ; Wijnants, Ernest ; Winders, Jean Jacques ; Yencesse, Hubert ; Zadkine, Ossip
biografie
Nederlands
boek